Analisis dan Perancangan Migrasi Jaringan dari IP4 Ke IP6 Pada PT.XYZ - Fuad Mumtaz (Jurnal Informatika dan Bisnis, 2014)
PT. XYZ is a company engaged in installation services / installation and networkmaintenance / maintenance IPv4 Information and Communication Technologies can be used ,then sooner or later the future global change network migration from IPv4 to IPv6 will forceexisting firms to adjust and make changes for structure -based IPv4 to IPv6 networks. PT. XYZrealizes that the company must anticipate changes in the future to begin to learn and implementIPv6 in enterprise networks . PT. XYZ also realized that with the advent of anticipating changefrom IPv4 to IPv6 networks based on a few years, then the company can take advantage ofbusiness opportunities that exist in terms of installation and maintenance services for IPv6network companies and government agencies in Indonesia. Method of transition or migration ofIPv4 to IPv6, including dual stack, tunneling and protocol translation. This research only includesa dual-stack and tunneling methods specifically tunneling. Besides 6to4 become one of the IPv6protocol will be very important in the future , also because there is still room for development ofIPv6 implementation . So this research is expected to be a reference for network administrators ornetwork engineers in PT. XYZ in implementing the migration from IPv4 to IPv6 networks basedin the future.